Modeling of financial flow regulators in systemic macroeconomic environment - Makarenko, I.P. (Математичне моделювання в економіці, 2017)
The peculiarities of macroeconomic influence on the innovation process of development in emerging market countries are explored. The emphasis is on economic mechanisms that create «instability zones» of monetary and fiscal policy instruments. The external and internal factors of their origin are determined. The monetary, financial and sociohumanitarian factors implementing the functions of redirection of financial flows are considered. The economic-mathematical approach to theoretical modeling the self-organization processes of economy is proposed.